ILO survey on social dialogue and pension reform in times of crisis and beyond: Slovenia - Guardiancich, Igor (Geneva, 2012)
"This paper examines the political economy of pension reforms in times of economic crisis and its impact on social dialogue and tripartite institutions in Slovenia. The Slovenian economy was badly hit by the global economic and financial crisis of 2008-2009, which was the worst crisis experienced by the country since the break-up of the former Yugoslavia. This crisis, combined with the pressure of financial markets and international institutions forced the government to initiate several reforms, including changes to the pension system."